Migration Control and Public Health: Restrictions to Human Mobility for Medical or Sanitary Reasons in times of Covid-19 Control migratorio y salud pública: restricciones a la movilidad humana por razones médicas o sanitarias en tiempos del Covid-19 - Mayorga Mc Donald, Ramon Victor (My University, 2021)
This paper analyzes (concerning the crisis of Covid-19) the past and present role of public health, limiting human mobility. Indeed, States have powers to restrict free movement, and eventually, exclude certain people who may be a danger to public health. However, any state decision that does this, must have a strictly epidemiological basis, and exclude any other type of considerations that, in practice, have affected human rights of migrants.
Keywords: control migratorio; migration control; pandemia; pandemic; public health; salud pública